Latency arbitrage when markets become faster - Burton Hollifield; Patrik Sandås; Andrew Todd (Sveriges Riksbank, 2017)
We measure the incidence of latency arbitrage for cross-listed stocks around the time of an exogenous shock that made the markets faster. Our sample is from NASDAQ Nordic and consists of Nordic blue chip firms listed and traded in multiple markets. We document a sharp decline in the incidence of cross-market arbitrage opportunities across the Nordic markets for cross-listed stocks from 2009 to 2010 and later. Over the five year sample period 77% of the observed cross-market arbitrage opportunities occurred in 2009 and 13% in 2010 and the remaining 10% spread over the last three years. The inside spread declines by, on average, 14.5 basis points or 53% from 2009 to 2013. Our results point to significant improvements in market effciency and market quality as a result of the switch to a faster trading system.
Keywords: G10; G14; G15; 330; Cross-market Arbitrage; Information Efficiency; High Frequency Trading